An Analysis Of Teacher's Technique On Speaking ClassAt Second Grade Of SMP N 1 Karangdowo - KURNIAWATY, IMMA; , Nur Hidayat M.Pd (2017)
This study aims to describe the techniques of teaching of speaking used by English teacher at SMP N 1 Karangdowo. Type of this research is a descriptive qualitative research mainly naturalistic studies in analyzing the data. Method of data collection in this research is the observation, interviews, and documentation. The results of this study showed that teachers in SMP N 1 Karangdowo in cooperation with native speakers in teaching speaking. Native speakers using the technique of conversation with different themes in each classes. Teacher and native speaker team up to form team teaching in teaching. The teacher acts as a controller and opener, while native speakers as convey the materials. The students also have a role as an active learner, as learners from other teaching resources, student is active, the monitor, and evaluators. The conclusion from this study is that English teacher in the SMP N 1 Karangdowo using the technique of learning speaking in conversation that could develop the capability of speaking students. The atmosphere in the class made fun in the absence of special material from books or other sources. This makes students more motivated to speak